2017
DOI: 10.1016/j.apsb.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

How to unleash mitochondrial apoptotic blockades to kill cancers?

Abstract: Apoptosis, especially the intrinsic mitochondrial cell death pathway, is regulated by the BCL-2 family of proteins. Defects in apoptotic machinery are one of the main mechanisms that cells employ to evade cell death and become cancerous. Targeting the apoptotic defects, either by direct inhibition of BCL-2 family proteins or through modulation of regulatory pathways, can restore cell sensitivity to cell death. This review will focus on the aspects of BCL-2 family proteins, their interactions with kinase pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 115 publications
(132 reference statements)
1
39
0
Order By: Relevance
“…BH3 mimetics have since been developed and proved capable of inhibiting BCL-2 clinically. For example, venetoclax (also known as ABT-199) was effective in clinical trials for refractory chronic lymphocytic leukaemia and is now advancing towards multiple trials for other malignancies 41 . In addition, preclinical studies indicate that targeting other pro-survival BCL-2 family members, particularly myeloid cell leukaemia 1 (MCL1) 42 , could be beneficial for the treatment of multiple cancer types and could quickly follow the same path.…”
Section: Where Are We Now In Terms Of Making These Targets Druggable?mentioning
confidence: 99%
“…BH3 mimetics have since been developed and proved capable of inhibiting BCL-2 clinically. For example, venetoclax (also known as ABT-199) was effective in clinical trials for refractory chronic lymphocytic leukaemia and is now advancing towards multiple trials for other malignancies 41 . In addition, preclinical studies indicate that targeting other pro-survival BCL-2 family members, particularly myeloid cell leukaemia 1 (MCL1) 42 , could be beneficial for the treatment of multiple cancer types and could quickly follow the same path.…”
Section: Where Are We Now In Terms Of Making These Targets Druggable?mentioning
confidence: 99%
“…Regretfully, ABT‐263 has a pronounced side effect: it provokes thrombocytopenia due to BCl‐xL dependence of platelets . So, up to now, ABT‐199 is the only BH3 mimetic to be approved by FDA for CLL clinical treatments . Bcl‐2 is dominated over Bcl‐xL in T‐ALL derived from ETP (ETP‐ALL), with an opposite situation at the more late maturation stages (DP, Fig.…”
Section: Targeting Mitochondria In Therapy Of T‐allmentioning
confidence: 99%
“…Direct and specific inhibitors against Mcl‐1 are so far lacking. The progress in the search of small compounds, selective against Mcl‐1, is summarized in recently published reports . Mcl‐1 plays a central role in chemoresistance to anti‐tubulin agents as vincristine.…”
Section: Targeting Mitochondria In Therapy Of T‐allmentioning
confidence: 99%
“…Antiapoptosis proteins include Bcl‐2, Bcl‐XL, and Mcl‐1, whereas proapoptosis proteins include Bak, Bax, Puma, and NOXA (Sochalska, Tuzlak, Egle & Villunger, ) Cytochrome C released from mitochondria is recruited to activate caspase‐9. Furthermore, the consequent release of cytochrome C and permeabilization of the mitochondrial outer membrane is regulated by a group of Bcl‐2 family proteins (J. Deng, ). In our reports, western blotting showed that Bcl‐2 and Bcl‐XL were downregulated, whereas Bak and Bax were unchanged when cells were exposed to different concentrations of PP‐22 (Figure c).…”
Section: Discussionmentioning
confidence: 99%